2017
DOI: 10.12788/jhm.2827
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Intensive Care Unit Psychiatric Comorbidity and Quality of Life

Abstract: The prevalence of psychiatric symptoms ranges from 17–44% in intensive care unit (ICU) survivors. The relationship between the comorbidity of psychiatric symptoms and quality of life (QoL) in ICU survivors has not been carefully examined. This study examined the relationship between psychiatric comorbidities and QoL in 58 survivors of ICU delirium. Patients completed three psychiatric screens at three months after discharge from the hospital: the Patient Health Questionnaire (PHQ-9) for depression, the General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…We confirm these findings by demonstrating that PTSD and depression are both associated with a considerable decrease in quality of life and that patients with psychological PICS have a worse quality of life compared to the general Dutch population in contrast with patients without psychological PICS. This is in line with a previous study by Wang et al, who demonstrated that the comorbidity of psychiatric symptoms is associated with a worse quality of life [33]. To improve the success of post-ICU clinics, treatment of psychological sequelae is critical to improve HRQoL.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We confirm these findings by demonstrating that PTSD and depression are both associated with a considerable decrease in quality of life and that patients with psychological PICS have a worse quality of life compared to the general Dutch population in contrast with patients without psychological PICS. This is in line with a previous study by Wang et al, who demonstrated that the comorbidity of psychiatric symptoms is associated with a worse quality of life [33]. To improve the success of post-ICU clinics, treatment of psychological sequelae is critical to improve HRQoL.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings go beyond describing the incidence of PICS in our cohort but clearly give a patient's opinion on the preference of needs and wishes on post-ICU interventions. To date, knowledge about the needs of patients suffering from PICS are scarce [33], and an effective treatment and thereby a uniform aftercare protocol is missing for patients suffering from PICS. Our findings can therefore be used to develop new treatment strategies, which can be implemented in an aftercare protocol in order to ameliorate the HRQoL of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…40,41,54,72 Previous or current ICU survivorship research has applied several of the PHQ scales. 8,13,[73][74][75][76] While the ultra-short depression and anxiety screening tool PHQ-4 is part of the proposed PICS screening, we suggest the 7-item Generalized Anxiety Disorder Scale (GAD-7) and the 8-item depression scale (PHQ-8) for the extended assessment. The measurement quality of the PHQ-8 is equivalent to that of the PHQ-9, which has an additional item for thoughts of death and self-harm.…”
Section: Feasibility and Measurement Properties Of The Proposed Omismentioning
confidence: 99%
“…Future studies will need to further examine the effectiveness of ICU survivor clinic, but a small longitudinal study of CCRC found beneficial effects on patients’ cognitive and functional symptoms. 62 One major concern is that although psychiatric morbidity in ICU survivors is associated with adverse effects on patients’ quality of life and increased acute care service utilization after discharge from the ICU, 43,65 the role of mental health professionals in these ICU survivorship models has not been well-defined.…”
Section: Prevention and Treatment Of Deliriummentioning
confidence: 99%